Choosing Your Pond: Location Choices and Relative Income - Bottan, Nicolas L.; Perez-Truglia, Ricardo (The Review of Economics and Statistics, 2022)
Do individuals care about their relative income? While this is a long-standing hypothesis, revealed-preference evidence remains elusive. We provide a unique test by studying residential choices: individuals often must choose between places with different income distributions, and as a result they “choose” their relative income. We conducted a field experiment with 1,080 senior medical students who participated in the National Resident Matching Program. We estimate their preferences by combining choice data, survey data on perceptions, and information-provision experiments. The evidence suggests that individuals care about their relative income and that these preferences differ across single and nonsingle individuals.